2019
DOI: 10.1186/s12891-019-2820-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prediction model for knee joint line orientation after high tibial osteotomy

Abstract: Background Maintenance of optimal knee joint line orientation (KJLO) is important after high tibial osteotomy (HTO). No tools, however, are currently available that could predict the value of postoperative KJLO before surgery. First, this study sought to determine the effects of various preoperative anatomical alignment parameters to postoperative KJLO. Based upon these analyses, we aimed to devise an equation that predicts the value of postoperative KJLO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
12
0
1
Order By: Relevance
“…In accordance with previous studies, higher preoperative mHKA and MPTA were also predictors of higher postoperative KJLO [9,14]. It was reasonable that higher mHKA might require a larger correction, which was supposed to result in greater obliquity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with previous studies, higher preoperative mHKA and MPTA were also predictors of higher postoperative KJLO [9,14]. It was reasonable that higher mHKA might require a larger correction, which was supposed to result in greater obliquity.…”
Section: Discussionsupporting
confidence: 90%
“…There have been several studies discussing preoperative parameters associated with greater postoperative knee joint line obliquity [9,14]. Preoperative mechanical hip-knee-ankle angle (mHKA), medial proximal tibial angle (MPTA) and joint line convergence angle (JCLA) are well-established predictors of postoperative abnormal joint obliquity.…”
Section: Introductionmentioning
confidence: 99%
“…Medial opening wedge high tibial osteotomy (OWHTO) is a reliable treatment option for medial compartment osteoarthritis with varus deformity in relatively young patients. 3,11,17,20 Because the osteotomy gap is related to complications such as loss of correction, it is important to manage the gap appropriately. 3 Autograft is considered the most effective graft for gap healing, 8,16,24 but autograft can cause additional morbidities at the donor site.…”
mentioning
confidence: 99%
“…3 However, although studies have reported factors associated with postoperative JLO, including preoperative JLO, correction angle, and medial proximal tibial angle (MPTA), a simple and accurate method to preoperatively predict postoperative knee JLO has not been introduced. 1,20 Changes in lower extremity alignment cause a compensatory reaction in the hip and ankle joints adjacent to the knee, and previous studies 9,17 have focused mainly on changes in the ankle joint. Because this compensation also occurs in the hip joint, resulting in adduction of the lower limb after OWHTO, the relationship between the hip joint and changes in JLO should be elucidated.…”
mentioning
confidence: 99%
“…3 However, although studies have reported factors associated with postoperative JLO, including preoperative JLO, correction angle, and medial proximal tibial angle (MPTA), a simple and accurate method to preoperatively predict postoperative knee JLO has not been introduced. 1,20…”
mentioning
confidence: 99%